Marketing advantages and sustainable competitiveness through branding for the supply chain of Islamic country. Issue 7 (17th February 2021) - Shahbaz, Muhammad Saeed; Javaid, Mudaser; Alam Kazmi, Syed Hasnain; Abbas, Qamar
Abstract : Purpose: Branding plays a vital role in the success of every organization and even industry. In Islamic countries, every organization must consider Sharia rules while strategy making. Nowadays, the supply chain is considered a major tool of branding and marketing. After an extensive literature review, it has been found that the studies that test the marketing advantages (MAs) and sustainable competitiveness through branding are scarce. The purpose of this study is to empirically examine the relationship between branding and MAs and mediating the role of sustainable competitiveness. Design/methodology/approach: This is a quantitative study. An instrument was adopted, and data were collected. The researchers tested the hypotheses from the survey data from 179 electronic organizations. The data ware analyzed through structural equation modeling to examine the proposed hypothesis of this study. Findings: The findings indicate that the relationship among dimensions of branding attitude and MAs were supported (expect reliability). Additionally, this study also revealed that a sustainable competitive variable plays a substantial role as a mediating variable in those relationships. Research limitations/implications: This study is a cross-sectional survey. Consequently, the limited sample size from the electric industry may affect the power of generalizability. The next study may be demonstrated for other industries to respect the nature of the branding and MAs among the managerial staff of other industries. Practical implications: This study will help managers to understand how to use the supply chain as branding for their MAs through sustainable competitiveness. Originality/value: This study adds practical value to the literature on sustainable competitive, branding and MA and supply chain. The study shows that sustainable competitiveness has varying mediating effects on industry value.